Groin pain and soccer players: male versus female occurrence - Karlsson, M. K.; Dahan, R.; Magnusson, H.; Nyquist, F.; Rosengren, B. E. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: Groin pain is common in soccer players. Comparison of results from different studies, especially between genders, is difficult as studies use different definitions and data collection procedures. Therefore we conducted a study of both male and female soccer players enabling direct gender comparison.